Slow movement cadence in bodybuilding and response in muscular hypertrophy - Vales, Layara do; Talaveira, Amanda; Soares, Ana Caroline; Nono, Isabela; Alves, Lorena; Santos, Fernando Pereira dos (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 39 No 76 (2023): Publicação Contínua, 2023)
It is part of the knowledge of professionals and students in the field of physical education that weight training has its greatest potential to reach hypertrophic results through manipulable variables, which, within an organized exercise program, comprises progressive load intensity, rest interval between sets, sum of total work volume, choice of exercises and rest between sessions. Within training stimuli, there is a variable that is often overestimated: cadence. In this article, we will bring results from studies that show whether the duration of the repetition of a movement in a weight training exercise promotes greater responses when the objective is muscle hypertrophy.